Clinical and laboratory profile of different dengue sub types in dengue virus infection - Chaudhuri, Niloy Gan; Vithyavathi, S.; Sankar, K. (International Journal of Research in Medical Sciences, 2016)
Background: Dengue infection, an arthropod-borne viral hemorrhagic fever is caused by Arbovirus of Flavivirus genus and transmitted by Aedes aegypti, Aedes albopictus. Liver involvement in dengue fever is manifested by the elevation of transaminases representing reactive hepatitis, due to direct attack of virus itself or the use of hepatotoxic drugs. The objective of the study was to investigate clinical and laboratory profile of different dengue sub type’s patients admitted for dengue fever. Methods: All the adult patients with clinical features such as fever and later confirmed positive by dengue serology test admitted as inpatients were included in the study. Vitals parameters and systemic examination were performed. Investigation of dengue serotology, liver function test, routine investigations like hemoglobin percentage, total count, ESR, packed cell volume, platelet count, partial thromboplastin and activated partial thromboplastin time, blood urea, serum creatinine, and blood sugar estimation were done. Results: On comparison of clinical signs in different dengue subgroups it was observed that the mean value of pulse, blood pressure and respiratory rate were significantly more deranged in the DSS group as compared to the DF group. Platelet count was significantly lower in all the sub groups whereas PT/aPTT was more dearranged in the DSS and DHF group as compared to the DF group. Comparison between the mean values of liver function test in different dengue sub groups had been shown, elevated transaminases, hypoproteinaemia and hypoalbuminaemia, in higher frequency in dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS) as compared to classical dengue fever (DF) (P values significant). SGOT was significantly higher than the SGPT levels and SGOT was much more elevated in the DSS sub group compared to the DFS and DF group. Conclusions: The liver enzymes serum aminotransferase levels were significantly raised in patients with dengue shock syndrome compared to other two groups. Serum aminotransferases directly correlate with severity of infection in all the sub groups. Patients with secondary dengue infection were more prone for developing bleeding manifestations and shock syndrome.